First record of Diploscapter coronata (Rhabditida), a possible health significance nematode associated with tomato crops in Argentina - Salas, Augusto (2017)
Diploscapter coronata is a free-living soil bacterial-feeding nematode found incompost, sewage or agricultural soil and as a facultative parasite of insects and vertebrates,even humans. The clinical symptoms include epigastric tenderness, diarrhea,crampy abdominal pain, weakness and nauseas. Also, they have been considered aspotential carriers of bacteria pathogenic to the surface of preharvest fruits and vegetablesin contact with soil. In this note, we reported the presence of D. coronata in the frameworkof diverse soil nematodes samplings in orchards of Abasto town, Buenos Aires province,Argentina. Soil samples taken from tomato growing (Lycopersicon esculentum) wereprocessed in the laboratory by the centrifugation method, while collected roots wereobserved directly under stereomicroscope in order to isolate nematodes. Specimenswere identified by morphological and morphometric characteristics. Results showed thepresence of D. coronata in agricultural soil and in association with root galls, caused bythe plant-parasitic nematode, Nacobbus aberrans. Females were the only isolated stage.The detection of this nematode in greenhouses where dogs, cats and poultry live togetherwithout any health control highlights the importance of applying proper hygiene measuresduring agricultural practices to avoid contamination of fruits and vegetables and preventinfections in domestic animals and humans. This report constitutes the first record of theDiploscapter genus with the species D. coronata in Argentina.